Importance of complex band structure and resonant states for tunneling - P.H. Dederichs; P. Mavropoulos; Wunnicke, O; N. Papanikolaou; Bellini, V; R. Zeller; Drchal, V; Kudrnovsky, J (JOURNAL OF MAGNETISM AND MAGNETIC MATERIALS, 2002)
The paper aims at understanding the tunneling process in epitaxial magnetic tunnel junctions. Firstly, we stress the importance of the complex band structure of the insulator for the tunneling of the metal electrons. For large insulator thicknesses the tunneling current is carried by very few states, i.e., those states in the gap of the semiconductor having the smallest imaginary component of the k-vector. In the case of GaAs, ZnSe and MgO these are Delta(1)-states at the Gamma-point. Secondly, we discuss the role of resonant interface states for tunneling. Based on simple model calculations and ab initio results we demonstrate that for symmetrical barriers the minority conductance can be dominated in an intermediate thickness range by few `hot spots' in the surface Brillouin zone, arising from resonant interface states. In these hot spots full transmission can still be obtained, when all other states are already strongly attenuated, so that the usual exponential decay can be considerably delayed. (C) 2002 Elsevier Science B.V. All rights reserved.